Integrating Task and Data Allocation Using a Parallel File System - Guardia, Hélio Crestana; Sato, Liria Matsumoto (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance Computing, 2000)
Parallel files combine several disks to provide increased storage capacity and fast data transfer between the primary and secondary memories. The use of parallel files by distributed applications however introduces new challenges to the parallel file system, which may inhibit the scalability of such applications. This work presents a study on the creation of a parallel file system that facilitates the development of distributed parallel applications with large amount of I/O operations. The proposed system was implemented and generated new tools that integrate file system operation with a mechanism for process creation and distribution. The evaluation of the system shows the viability of its utilization allowing the scalability of a distributed parallel application.